Factors Associated with the Incidence of Deaths in Traffic Accidents on Federal Highways in the State of Santa Catarina - Brazil - Borba Broering , Wellington; Schoenhals Delavy , Francieli; Konrath , Andrea Cristina Konrath; Nakamura , Luiz Ricardo; do Carmo Comparsi de Vargas , Vera (Revista Transporte y Territorio, 2022)
The present research sought to investigate, through a logistic regression model, how certain factors can contribute to the occurrence of fatal accidents on federal highways in the state of Santa Catarina -Brazil. Thus, public data from the Federal Highway Police on accidents that occurred from 2007 to 2018 were used. The final logistic model allowed to establishment the odds ratio of the main categories among the variables of meteorological condition, phases of the day, causes of the accident, type of accident and route layout. Factors such as frontal collision, run over, dawn, road/environmental cause and sunny conditions were the most representative in this context. Elements associated with the lack of central medians and pedestrian walkways, low visibility while driving and fatigue at the steering wheel were major contributors to the increased severity of collisions. The greatest odds ratios for the road/environmental factors and sunny condition were considered unexpected results, against the premise that the human factor and wet conditions contribute more significantly to the occurrence of deaths. The lack of information about the condition of the road at the time of the accident, the volume of traffic on the highways and the type of vehicle were limiting factors for the study.